Legal Literacy Training for Christian Church Leaders: A Community Development Program in Donomulyo, South Malang, Indonesia - Edi Purwanto (Actual Insight, 2026)
Legal literacy plays a crucial role in helping religious leaders navigate legal frameworks related to religious freedom, public communication, and community relations in plural societies. However, many church leaders in local communities still have a limited understanding of legal regulations governing religious practices, which may lead to misunderstandings or potential social tensions. This study reports the implementation of a legal literacy training program for Christian church leaders in Donomulyo, South Malang, Indonesia. The program was designed as a community development initiative aimed at strengthening legal awareness among religious leaders through participatory education. The training involved more than 80 church leaders from various congregations and was conducted through seminars, interactive discussions, and a simple knowledge evaluation using pre-test and post-test instruments. The results indicate a significant improvement in participants’ legal knowledge, with the average score increasing from 53.78 in the pre-test to 74.27 in the post-test. Participants also demonstrated strong engagement during discussions and expressed intentions to disseminate the knowledge gained within their congregations. These findings suggest that legal literacy training can serve as an effective community empowerment strategy by strengthening the capacity of religious leaders to navigate legal issues, promote responsible public communication, and support social harmony in pluralistic communities.